DOES FIRM GROWTH MODERATE THE IMPACT OF WORKING CAPITAL MANAGEMENT ON PROFITABILITY? EVIDENCE FROM LQ45 FIRMS : DOES FIRM GROWTH MODERATE THE IMPACT OF WORKING CAPITAL MANAGEMENT ON PROFITABILITY? EVIDENCE FROM LQ45 FIRMS - Rahayu, Gita; Efriani, Betharia; Lathifah, Azmii (TECHNOBIZ : International Journal of Business, 2026)
This study examines the importance of profitability as a key indicator for investors in assessing a company’s ability to generate profits and pay dividends, while also considering managerial share ownership as a factor influencing company performance. It aims to analyze the effect of working capital turnover, inventory turnover, and accounts receivable turnover on profitability, as well as the role of company growth as a moderating variable, using a sample of 40 LQ45 companies listed on the Indonesia Stock Exchange during 2020–2024 with data collected from financial statements. The results, analyzed using multiple regression and Moderated Regression Analysis (MRA), show that working capital turnover, inventory turnover, and accounts receivable turnover significantly affect profitability, and company growth successfully moderates these relationships.